Analisis Persepsi Rasionalitas Investor di Pasar Modal Indonesia - Astri Wening Perwitasari; Iwan Hendra Kusuma; Setiyono - Setiyono (FE Program Studi Manajemen, 2020)
Rationality is an old assumption upheld by traditional finance theory. The existence of rationality in investors is starting to be doubted by financial behavior theory. This study aims to determine investor perception in capital market investment. The study population is investors in the capital market and sampling was done by simple random sampling method. Primary data were obtained through questionnaires of 54 respondents and will be analyzed using quantitative descriptive analysis with the mean arithmetic methods. The results of the questionnaire measurement were first tested for validity and reliability. The analysis shows that the percentage of investor rationality perception is high (76.18%). The mean value of each indicator is also high, i.e. investors searching or having as much information as possible (7.79), investors are able to conduct investment analyzes with their information (7.85), investors diversify investment and create optimal portfolios (7.57 ), investors monitor and supervise investments (7.43), and investors tend to have difficulty changing investment decisions that have been taken (7.07). While indicator that show investor-oriented for long-term investment has a very high mean value (8.18).